Empirical evidence linking futures price movements of biofuel crops and conventional energy fuel - Liu,J. (Springer Verlag, 2015)
© Springer International Publishing Switzerland 2015. This study proposes a dynamic vine copula based ARMAX-GARCH model to explore the dependence structures between energy futures and agricultural futures, and between corn future and soybean future conditional on energy futures etc. The more important thing is that we employ the empirical results of dynamic vine copulas to forecast the expected shortfall (ES) and the optimal portfolio weights (OPW) based on minimum ES and Monte Carlo simulation method results showed that the appropriate margins were skewed student t distribution for soybean future return, and student t distribution for crude oil, palm oil and corn future returns, and the time-varying copulas T copula, R-BB8(180◦), R-BB8(180◦), Gaussian copula, R-Joe(180◦) and T copula can preferably capture the dependences compared with static copulas in C-vine copula structure. Moreover, we found that the values of ES will converge to −0.0121,−0.0145 and −0.0164 at period t+1 under 5, 2 and 1% level, respectively. Meanwhile, As long as we invest in strict accordance with the optimal portfolio weights, the ES will reduce 56, 54 and 53% at 5, 2 and 1% level, respectively.